Amino-functionalized Ti3C2Tx with anti-corrosive/wear function for waterborne epoxy coating. (1st October 2020) - Yan, Han; Cai, Meng; Li, Wen; Fan, Xiaoqiang; Zhu, Minhao
Abstract: Two-dimensional Ti3 C2 T x flakes have great application potential in various areas due to their optical, electronic, electrochemical and mechanical properties, but their anti-corrosion and wear-resistance performance were not well understood. The difficulties in achieving good dispersity and interface interaction of inorganic additives in organic coatings hinder the incorporation of Ti3 C2 T x into the epoxy coating. Here, few-layered Ti3 C2 T x sheets with amino-functionalization were prepared, and as reinforced-additives were added into the waterborne epoxy coating. Anti-corrosion and tribological properties of as-prepared composite coatings were investigated in detail. The results reveal that the composite coating with 0.5 wt.% amino-functionalized Ti3 C2 T x sheets shows excellent corrosion protection (the lowest frequency impedance was 3.12 × 10 9 Ω cm 2 ) and wear resistance (wear rate was reduced by 72.74%). The greatly improving performance of composite coatings mainly depends on: (a) good dispersity and compatibility of amino-functionalized Ti3 C2 T x in organic matrix, (b) high adhesion strength between coating and metal substrate and (c) the intrinsic properties of Ti3 C2 T x sheets. The work provides a good path for applications of MXene as multifunctional additives.